Assistance the Packaging of Literacy Learning Materials in Digital Formats for Elementary School Teachers in Kendari City - Rimba Hamid; La Ili; Yoo Eka Yana Kansil (Prodi PGSD FIP UNM, 2020)
The activity of assisting the packaging of literacy learning materials in digital format for elementary school teachers in partner schools in this community partnership program, namely: SDN 85 Kendari and SD IT Al-Kalam Kendari becomes very important, bearing in mind the two schools have implemented a school literacy program in which one of the activities is integrating the activity of reading and writing at the beginning of learning for 15-20 minutes. The main objective of the assisting activity is to improve teacher skills in packaging varied learning materials, especially those with the digital format needed in literacy activities on learning themes in elementary schools. The method used in this community partnership program was the assistance of packaging literacy learning materials in digital format for use in learning. The implementation of the community partnership program in the form of mentoring produced a product in the form of digital format literacy learning materials whose effectiveness would be evaluated through the implementation in the implementation of learning, especially in the literacy activity segment at the beginning of the core activity. The evaluation was based on the reflection of the teachers who used this product after activities were carried out. The main obstacle found in this mentoring activity was the inadequacy of the ability of some teachers to operate the main supporting applications (such as power points) as well as the low ability to find digital learning resources on the pages that have been shown at the time of mentoring